Measurement of Indicators of Industrial Food Processes Through Artificial Intelligence. - Santiana Espín, Cristian Germán; Buenaño Moyano, Luis Fernando; Andrade Albán, María José; Padilla Padilla, Celin Abad (Journal of Namibian Studies)
Accurate measurement of food industrial process indicators is critical to ensuring product quality and safety. In this article, we propose the use of artificial intelligence (AI) as an efficient and accurate tool to measure and monitor these indicators. A methodology based on AI techniques is described, which includes real-time data processing and predictive model generation. The results obtained demonstrate that AI can significantly improve the measurement of indicators, reduce costs and increase the efficiency of industrial food processes. In conclusion, the implementation of artificial intelligence in the measurement of indicators of industrial food processes offers great advantages and benefits for the food industry.